Pott’s Disease with Incidentally Discovered Multiple Brain Tuberculomas in a Previously Healthy 10-Year-Old Girl - May Albarrak; Abdulrahaman Alodayani; Nasir Al Otaibi; Yasser Albrikeet (Case Reports in Infectious Diseases)
Pott’s disease (PD) represents the most common form of spinal tuberculosis. Its association with brain tuberculomas is extremely rare. Herein, we report a previously healthy child with PD and concurrent multiple brain tuberculomas who was successfully treated with antituberculous therapy, surgical drainage of the paravertebral abscess, and adjuvant steroid therapy.